A Bidentate Ligand Featuring Ditopic Lewis Acids in the Second Sphere for Selective Substrate Capture and Activation. Issue 13 (20th February 2023) - Beagan, Daniel M.; Kiernicki, John J.; Zeller, Matthias; Szymczak, Nathaniel K.
Abstract: We present a ligand platform featuring appended ditopic Lewis acids to facilitate capture/activation of diatomic substrates. We show that incorporation of two 9‐borabicyclo[3.3.1]nonane (9‐BBN) units on a single carbon tethered to a pyridine pyrazole scaffold maintains a set of unquenched nitrogen donors available to coordinate Fe II, Zn II, and Ni II . Using hydride ion affinity and competition experiments, we establish an additive effect for ditopic secondary sphere boranes, compared to the monotopic analogue. These effects are exploited to achieve high selectivity for binding NO2 − in the presence of competitive anions such as F − and NO3 − . Finally, we demonstrate hydrazine capture within the second‐sphere of metal complexes, followed by unique activation pathways to generate hydrazido and diazene ligands on Zn and Fe, respectively. Abstract : We report the synthesis of a bidentate ligand featuring secondary sphere ditopic Lewis acids. We verify a Lewis acid additivity effect for the ditopic boranes compared to a monotopic analogue using hydride ion affinity and competition studies. We show chemoselective nitrite capture in the presence of other anions. Pre‐organized hydrazine adducts in the second sphere of Zn and Fe are functionalized to hydrazido and diazene ligands, respectively.